Uniform Crime Reporting Program Data (United States): County Level Arrest and Offenses Data, 1977-1983 ([Verlag nicht ermittelbar], 1988)
The files in this collection contain counts of arrests and offenses for UCR index crimes: murder, rape, robbery, assault, burglary, larceny, auto theft, and arson. County populations are also reported.